EVALUASI NILAI GIZI TEPUNG PRA-MASAK PISANG TANDUK DAN PISANG RAJA NANGKA [Nutritional Evaluation of Pre-cooked “Tanduk” and “Raja Nangka” Plantain flour] - . Rosida; Dedin Finatsiyatull Rosida (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2011)
This research dealt with the nutritional evaluation of pre-cooked plantain flour in experimental Wistar rats to evaluate physical and chemical properties of the digesta of rats as well as glucose and cholesterol content of their blood. Pre-cooked plantain flour was made of 2 types of plantain, Tanduk plantain (Musa corniculata) and Raja Nangka plantain (Musa paradisiacalLinn) which have been heated and cooled under 3 conditions (boiling-cooling, steaming-cooling, and baking-cooling, prior to drying and milling. It was found that both pre-cooked plantain flours have high resistant starch content (6.38-11.40%). Nutritional evaluation of rats for 20 days treatment revealed that pre-cooked plantain flour diets have no effect on the volume, weight, water content, and pH of the digesta and glucose content of the blood serum. But these diets increase the concentration of acetic acid, propionic acid and butyric acid of the digesta and decrease cholesterol content of the blood serum, especially Tanduk plantain pre-cooked flour made from Tanduk plantain after boiling and cooling, hence it has good effects on the colonic microbiota.